ASPEK HUKUM PENGGUNAAN SOSIAL MEDIA SESUAI UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 - Mahayoni Mahayoni (President University, 2017)
Social media nowadays has been a familiar word to our ears. In less than two decades, the revolutionary changes have occurred among the various circle of society. The needs of online services recently through a wireless or wifi has been the basic need for the society, especially the urban . Whats app , twitter , instagram , face book , and other types of applications are becoming familiar to our ears. Almost the entire range of social community change remarkably by the social media. This online social media community is a new order that its presence has an important role in the life of socialization, national and state life. Nevertheless, this new world order that arises around us moves very fast and exponential. The society be stutter and are still not ready to face this new world order. Their Expression of feeling which they used to undertake directly to others in a limited number and confidential are now shed in the notes on the new world order. The sense that supposedly undetermined to be right and wrong and located in private area of somebody is now can be seen and read by public. As result, people can respond or giving different comments. The possibilities of incorrect notions, or consideration in cornering others to be an untrue information often occur . The role of social media also helpful as a social control. This is an extraordinarily benefit. The case of officer police who ask for a bribe that went viral in the world of social media to the case of a group of teenagers gave the red wine to a horse in Safari Park spread quickly and police act quickly. On this side, there are also people who deliberately uses the social media to express hatred,distaste , or disagreement against an attitude, the act, or policy are also on the rise sharp. In fact this group is also acting further by made up a fake news which is untrue just to satisfy their hatred. The large number of this incident made police officer were unable to go to control the situation. The general community are the victim because they suffer losses due to many parties continue the destructive action that could harm the united of nation. It is a home work to utilize social media to bring more advantages that disadvantages.